Source Analysis of Event-related Cortical Activity during Visuo-spatial Attention - Di Russo, Francesco; Martínez, Antigona; Hillyard, Steven A. (Cerebral cortex (New York, N.Y. 1991), 2003)
Recordings of event-related potentials (ERPs) were combined with structural and functional magnetic resonance imaging (fMRI) to study the spatio-temporal patterns of cortical activity that underlie visual–spatial attention. Small checkerboard stimuli were flashed in random order to the four quadrants of the visual field at a rapid rate while subjects attended to stimuli in one quadrant at a time. Attended stimuli elicited enhanced ERP components in the latency range 80–200 ms that were co-localized with fMRI activations in multiple extrastriate cortical regions. The earliest ERP component (C1 at 50–90 ms) was unaffected by attention and was localized by dipole modeling to calcarine cortex. A longer latency deflection in the 150–225 ms range that was accounted for by this same calcarine source, however, did show consistent modulation with attention. This late attention effect, like the C1, inverted in polarity for upper versus lower field stimuli, consistent with a neural generator in primary visual cortex (area V1). These results provide support to current hypotheses that spatial attention in humans is associated with delayed feedback to area V1 from higher extrastriate areas that may have the function of improving the salience of stimuli at attended locations.